ANALISIS PENGARUH PEMASARAN HIJAU TERHADAP CITRA MEREK DAN KEPUTUSAN PEMBELIAN AQUA DAN LE MINERALE - Dewi Nusraningrum; Tri Mayang Mekar; Jajang Gunawijaya (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2021)
The growing environmental damage is the reason for the need for green marketing as a marketing strategy that supports the environment by creating environmental benefits based on consumers' expectations. Green marketing can be done by manipulating the four marketing mix elements to sell products and services offered from environmental conservation benefits derived from waste reduction, increased energy efficiency, and reduced toxic emissions. This study analyzes the effect of green marketing on brand image and purchasing decisions. The population of this study was consumers in Jakarta. Questionnaires were distributed online to 180 respondents reached by researchers. The data obtained is processed by using SmartPLS. The results show that green marketing has a positive and significant effect on brand image and purchasing decisions. Moreover, the brand image positively affects purchasing decisions.